Broadcasting Laboratory Impression Management Strategy in Building the Image of IAIN Bone - Qudratulah; Rosniar; Wild Ananta (Research Institute and Community Engagement of UIN MADURA, 2023)
This research aims to examine the impression management strategy of the Broadcasting Laboratory in building the image of IAIN Bone. This research presents an image or image strategy that shapes IAIN Bone's reputation as an organization with impression management carried out by the organization through social media broadcasts. The research uses descriptive qualitative research methods. This research design uses a case study with a communication scientific approach. Data collection techniques were carried out using observation, interviews, FGD, and documentation. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. The dominance of self-promotion strategies implemented by the Broadcasting Laboratory surpasses four other impression management strategies. Of course, this refers to the way branding image is built by highlighting positive things by mentioning the abilities they have. The ingratiation strategy carried out by the Broadcasting Laboratory further strengthens the characteristics of a humanist campus with an impression of attention from the audience because there are reasons to assess IAIN Bone such as Islamic, up to date, superior, humanist, and so on. Intimidation strategy, the video shown tries to get attention and is expected to give a favorable impression to the audience. The intimidation strategy is not widely implemented by the IAIN Bone Broadcasting Laboratory because it has the opportunity for conflicting arguments in cyberspace. In line with that, the Supplication strategy is also a strategy that is rarely used in the production of IAIN Bone Television and Radio Broadcasting Laboratory programs. The supplication strategy is considered a natural strategy that is rarely used by the “Sky News” production team to give a more natural impression of everything that happens at IAIN Bone. (Penelitian ini bertujuan mengkaji strategi impression management Laboratorium Penyiaran dalam membangun Citra IAIN Bone. Penelitian ini menyajikan strategi gambaran atau kesan citra yang membentuk reputasi IAIN Bone suatu organisasi dengan impression management yang dilakukan oleh organisasi melalui siaran media sosial dengan. Penelitian menggunakan metode penelitian deskriptif kualitatif. Desain penelitian ini menggunakan Studi kasus dengan pendekatan keilmuan Komunikasi. Teknik pengumpulan data dilakukan dengan observasi, wawancara, FGD, dan dokumentasi. penelitian. Teknik analisis data dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Dominasi strategi self-promotion diterapkan Laboratorium Penyiaran melaempat strategi impression management yang lainnya. Tentu hal ini merujuk sebagaimana branding image dibangun dengan menonjolkan hal-hal yang positif dengan menyebutkan kemampuan-kemampuan yang dimiliki. Strategi ingratiation yang dilakukan Laboratorium Penyiaran semakin memperkuat ciri khas kampus yang humanis dengan kesan yang perhatian dari khalayak karena adanya alasan untuk menilai IAIN Bone seperti Islami, up to date, unggul, humanis, dan sebagainya. Strategi intimidation, video yang ditayangkan berupaya mendapat perhatian dan diharapkan mendapat kesan yang disukai oleh khalayak. Strategi intimidation tidak banyak diterapkan oleh Laboratorium Penyiaran IAIN Bone karena memiliki peluang terjadinya konflik pertentangan argumentasi di dunia maya. Sejalan dengan itu, strategi Supplication juga strategi yang jarang dilakukan dalam produksi program Laboratorium Penyiaran Televisi dan Radio IAIN Bone. Strategi supplication dianggap wajar menjadi strategi yang jarang dilakukan oleh tim produksi Sky News untuk memberikan kesan yang lebih natural dari segala hal yang terjadi di IAIN Bone.)